Chemical Characterization of Powdered Broth from the Use of Catfish Head Extract and Mulberry Fruit - Alvianita, Bella; Finatsiyatull Rosida , Dedin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
One dried product that can enhance flavor in various food products is powdered broth. Glutamic acid is the main compound responsible for the umami taste in powdered broth products. This compound is naturally present in raw materials such as patin fish headss and mulberry fruit, which were used as the main components in this study. This research aimed to examine how different amounts of patin fish head extract and mulberry fruit liquid, along with varying levels of maltodextrin, affect the qualities of the powdered broth produced. The study employed a completely randomized design (CRD) with a two-factor factorial pattern. The first factor was the ratio of patin fish head extract to mulberry filtrate (1:2, 1:1, and 2:1), and the second factor was maltodextrin concentration (10%, 15%, and 20%). We analyzed the data using 5% ANOVA, and if we found significant differences, we proceeded with DMRT tests. The results indicated that the optimal treatment was the extract ratio of patin fishhead to mulberry (2:1) with a 10% maltodextrin addition. The resulting powdered broth had a moisture content of 14.80%, ash content of 1.88%, fat content of 6.08%, protein content of 12.06%, carbohydrate content of 66.41%, and yield of 12.56%. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production